The β‐adrenoceptor blocker propranolol ameliorates compulsive‐like gambling behaviour in a rodent slot machine task: implications for iatrogenic gambling disorder. (3rd August 2018) - Cocker, P. J.; Lin, M. Y.; Tremblay, M.; Kaur, S.; Winstanley, C. A.
Abstract: Previous work has shown that chronic administration of the dopamine D2/3 receptor agonist ropinirole invigorates performance on a rodent slot machine task (rSMT). This behavioural change appears superficially similar to the iatrogenic gambling disorder (GD) observed in a sub‐set of patients with Parkinson's disease (PD), and has been associated with increased activation of the intra‐cellular signalling proteins GSK3β and CREB in the striatum. Here, we wanted to determine whether this response to ropinirole could be attenuated by targeting these signalling proteins, and if the loss of dopaminergic innervation characteristic of PD would alter ropinirole's effects on the rSMT. Male Long Evans rats were trained on the rSMT. Dopaminergic terminals innervating the dorsolateral striatum were then lesioned bilaterally using the neurotoxin 6‐hydroxydopamine hydrochloride (6‐OHDA). Subsequently animals were implanted with osmotic mini‐pumps delivering ropinirole. Lastly, animals were given dietary lithium (Li + ), to inhibit the activation of GSK3β, or injections of the ß‐adrenoceptor antagonist propranolol, which potently inhibits CREB as a secondary mechanism of action, and any changes in ropinirole‐induced increases in compulsive‐like engagement in the rSMT evaluated. Chronic ropinirole increased the number of trials animals completed, reproducing our original finding. This increase in task engagement was not altered in animals with 6‐OHDA lesions, a putative model of early PD. In addition, the effects of ropinirole were not attenuated by administration of Li +, but were ameliorated by propranolol. These data suggest that propranolol may represent a potential pharmacotherapy for the treatment of iatrogenic gambling. Abstract : Chronic administration of the dopamine D2/3 agonist ropinirole produced compulsive‐like task engagement on a rodent slot machine task, in a manner potentially analogous to the iatrogenic gambling observed in a sub‐set of patients with Parkinson's disease. Administration of the ß‐adrenoceptor antagonist propranolol ameliorated animals' compulsive task engagement, suggesting that propranolol represents a potential pharmacotherapy for the treatment of iatrogenic gambling.